Land Surface Temperature investigation of Babylon city between (2002-2022) using Remote Sensing and GIS Technique - Al-Aarajy, Khalid H. Abbas; Hassan, Zainab H. Mohammed (Iraqi Journal of Science, 2023)
Land surface temperature (LST) is crucial for determining the region's environmental quality because a significant temperature rise causes disasters, which cause environmental imbalance, reducing biodiversity and hastening desertification. In this study, remote sensing and geographic information systems were used to estimate the change in the LST of Babylon, Iraq, using two satellite images taken 20 years apart (2002, 2022). The temperature was extracted using a specific mathematical model in ArcMap10.8 software. The findings demonstrated a significant variation in temperatures and the concentration in various regions of Babylon between 2002 and 2022 and the relationship between LST and Normalized difference vegetation index. The most significant element that causes a shift in the LST is the spread of urbanization in Babylon at the expense of vegetation and unused land.